COVID19-related and all-cause mortality risk among middle-aged and older adults across the first epidemic wave of SARS-COV-2 infection: a population-based cohort study in Southern Catalonia, Spain, March-June 2020 - Angel Vila-Corcoles; Eva Satue-Gracia; Angel Vila-Rovira; Cinta de Diego-Cabanes; Maria Jose Forcadell-Peris; Immaculada Hospital-Guardiola; Olga Ochoa-Gondar; Josep Basora-Gallisa (BMC, 2021)
Abstract Background Direct and indirect COVID19-related mortality is uncertain. This study investigated all-cause and COVID19-related deaths among middle-aged and older adults during the first wave of COVID-19 pandemic period, assessing mortality risks by pre-existing socio-demographic and medical underlying conditions. Methods Population-based cohort study involving 79,083 individuals ≥50 years-old in Tarragona (Southern Catalonia, Spain). Baseline cohort characteristics (age/sex, comorbidities and medications/vaccinations history) were established at study start (01/03/2020) and main outcomes were COVID19-related deaths (those occurred among patients with laboratory-confirmed COVID19) and all-cause deaths occurred among cohort members between 01/03/2020-30/06/2020. Mortality risks were assessed by Cox regression analyses. Results Cohort members were followed for 1,356,358 persons-weeks, occurring 576 all-cause deaths (124 COVID19-related deaths). Of the 124 deceased patients with a laboratory-confirmed COVID19, 112 (90.3%) died by (due to) COVID-19, while 12 (9.7%) died with COVID-19 (but likely due to other concomitant causes). All-cause mortality rate among cohort members across study period was 42.5 deaths per 100,000 persons-week, being 22.8 among healthy/unrelated-COVID19 subjects, 236.4 in COVID19-excluded/PCR-negative subjects, 493.7 in COVID19-compatible/PCR-unperformed subjects and 4009.1 in COVID19-confirmed patients. Increasing age, sex male, nursing-home residence, cancer, neurologic, cardiac or liver disease, receiving diuretics, systemic corticosteroids, proton-pump inhibitors and benzodiazepines were associated with increased risk of all-cause mortality; conversely, receiving renin-angiotensin inhibitors and statins were associated with reduced risk. Age/years (hazard ratio [HR]: 1.08; 95% confidence interval [CI]: 1.06-1.10), sex male (HR: 1.82; 95% CI: 1.24-2.70), nursing-home residence (HR: 12.56; 95% CI: 8.07-19.54) and number of pre-existing comorbidities (HR: 1.14; 95% CI: 1.01-1.29) were significant predictors for COVID19-related mortality, but none specific comorbidity emerged significantly associated with an increased risk in multivariable analysis evaluating it. Conclusion COVID19-related deaths represented more than 20 % of all-cause mortality occurred among middle-aged and older adults during the first wave of the pandemic in the region. A considerable proportion (around 10 %) of these COVID19-related deaths could be attributed to other concomitant causes. Theoretically COVID19-excluded subjects (PCR-negative) suffered ten-times greater all-cause mortality than healthy/unrelated-COVID19 subjects, which points to the existence of considerable number of false negative results in earlier PCR testing and could explain part of the global excess all-cause mortality observed during the pandemic.